Carrying CapacitySungai Paku Reservoir Based on Total-P in Kampar Kiri District Kampar Regency Riau Province - Nadira, Ismi; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract            A carrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. The study aimed to determine the aquatic carrying capacity for aquaculture fishing of Sungai Paku Reservoir, Kampar Kiri District Kampar Regency Riau Province. The carrying capacity is determined based on Total-P concentration. The research was conducted during June to July 2019. Water samples were taken in three stations, namely Station 1 (riverine zone), Station 2 (transition zone), and Station 3 (lacustrine zone). In each stasions, there were 3 sampling point, in the surface, in two Secchi depth, and in four Secchi depth. Sampling was done three times, once/week. Water quality parameters measured were Total-P, transparency, temperature, depth, pH, Dissolved Oxygen, and BOD5. Carrying capacity was analyzed using the Beveridge formula (1984). Result shown the concentration of Total-P: 0.056–0.176 mg/L, transparency: 69.1-80.8 cm, temperature: 28-30 °C, depth: 4.2-6.5 m, pH: 5, Dissolved Oxygen: 2.08-5.19 mg/L, BOD5: 3.41-8.84 mg/L. Carrying capacity of Paku reservoir was 1432.9 kg/th, and number units floating cage can be operated was 6 unit. The current number of floating net cages (FNC) unit in Sungai Paku Reservoir was 12 units. Based on data obtained it can be concluded that the number of KJA have exceeded the reservoir carrying capacity. Keywords:Carrying capacity, Total-P, and floating net cages (FNC)